ON PHYSICAL ANALOGUES PROCESSES FOR PLASMA - Kozhevnikov, Y.; Nikolaev, V. (Energy and Automation, 2016)
This article looks atinnovative ways toassessthe plasma particlesfrom the viewpoint ofmechanics andelectrodynamics of movingcharged particles, and the use of the theory ofcontinuum mechanics andrelativisticmechanics.